29 Jun, 2021 03:01 PM

need help doing this problem in substitution?

ok please help 4x-2y=1 4x+3y=6 your help is greatly appreciated.

See Answer 10 Add Answers
Answer
Answer
NI
29 Jun, 2021 03:01 PM

To solve this by substitution, first pick a variable and an equation you'll use to solve for it. I'll use 4x-2y=1 to solve for y ... 4x-2y=1.....-2y=1-4x .......... y= -1/2  2x Now plug that in for y in the other equation and solve for x ... 4x 3y=6 ........ 4x 3(-1/2  2x )=6 ..... 4x - 3/2   6x= 6  (I'm sure you can take it from here to solve for x.)

LA
29 Jun, 2021 03:02 PM

Subtract first equation from second equation.

(4x + 3y) - (4x - 2y) = 6 - 1

5y = 5

y = 1

Substitute the value of y we get 4x -2 = 1

4x = 3

x = 3/4